(untitled) (Cardiovascular Journal, 2010)
Back ground: Reduction of coronary heart disease (CHD) risk through the modification of risk factors has a strong effect on clinical practice. The introduction of 3-hydroxy-3-methylglutaryl coenzyme-A (HMG-CoA) reductase inhibitors (statins) has significantly advanced the treatment of hypercholesterolemia and in reduction of cardiovascular events and total mortality rates. Among the available statins, Fluvastatin is a newer, synthetic, second generation, potent lipid lowering agent and widely accepted in diverse population. However the safety profile and efficacy was not assessed in Bangladeshi population, a population significantly different from Caucasian population where most studies were done. Current study aimed at evaluating the safety and efficacy of fluvastatin in the specified population. Methods: The study is an open-label, multicenter, quasi experimental study conducted among 162 adult patients suffering from hypercholesterolemia. After through baseline evaluation, the patients were given with Fluvastatin 80 mg once daily for 3 months. All the patients were assessed twice, before and after treatment. Data on demography, of relevant medical history and of physical examination were collected in the both the visit along with data on relevant lipid parameters (Total Cholesterol, LDL-C, HDL-C and TG) were collected at final visit. Safety was assessed by evaluating adverse events, as well as laboratory abnormalities, including liver aminotransferases. Results: Serum total cholesterol was found to be significantly reduced and across two assessments the reduction was 51.2 units (P<.001). Average reduction in LDL-cholesterol was around 40 units (P<.001). Most significant reduction (140.0±305.8 units) was seen in serum LDL cholesterol (P<.001). However; no statistically significant reduction was seen in HLD cholesterol. Safety of fluvastatin was assessed by evaluating the adverse events, as well as through laboratory abnormalities, including alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Comparison of aminotransferase level was done before and after treatment through paired t test, Neither ALT nor the AST showed statistically significant rise after 3 months treatment of fluvastatin (P>.05). Out of 162 study participant 4.3% had their treatment interrupted, of which 1 (0.62%) had to cease treatment due to lack of efficacy, 1 (0.62%) experienced adverse event, 2 (1.24%) didn’t return to follow-up and 3 (1.86%) patients requested their physician to cease the treatment. Conclusion: Three month treatment with Fluvastatin XL 80 mg reduces most of lipid parameter of lipid profile (Total cholesterol, Triglyceride and LDL) significantly. The drug is found to be well tolerated with minimal adverse event during the course of treatment. Key words: Hypercholesterolemia; Dyslipidemia; Lipid lowering agent; Fluvastatin. DOI: 10.3329/cardio.v2i2.6631 Cardiovasc. j. 2010; 2(2) : 147-155